(x + 4) ² = 9x + 22
( ) -2 e 3
( )-2 e-3
( )-1 e 9
(4e 9
Soluções para a tarefa
Respondido por
0
Resposta:
Olá boa noite
segue a resolução no print
Anexos:
![](https://pt-static.z-dn.net/files/dfa/c2bf81e1c0e4eaefde251da5445dbc51.jpg)
Respondido por
0
Resposta:
Explicação passo-a-passo:
=
Δ= . -4. 1 . -6
Δ= 1 + 24 = 25
x1 = = 3
x2 = = -2
Ou seja, (X) -2 e 3
Espero ter ajudado!
Perguntas interessantes
Português,
9 meses atrás
Ed. Física,
9 meses atrás
Português,
9 meses atrás
Português,
11 meses atrás
Matemática,
11 meses atrás
História,
1 ano atrás
Química,
1 ano atrás
Ed. Técnica,
1 ano atrás